Syphillis In Pregnancy: A Literature Review - I Putu Bagus Mulyana Yoga; Anak Agung Gede Raka Budayasa (Syntax Corporation, 2022)
Syphilis is a bacterial sexually transmitted disease (STI) caused by Treponema pallidum. Syphilis can be transmitted through sexual contact, blood transfusion and vertical transmission from mother-to-child. Syphilis in pregnancy that is left untreated might lead to miscarriage, stillbirth, neonatal death, premature birth, low birth weight, and congenital syphilis. Syphilis in pregnancy, although results in high morbidity and mortality, is actually preventable through early screening and treatment. Diagnosis of syphilis in pregnancy is made through history taking, physical examination, laboratory testing and radiology. Screening for syphilis in pregnant women is important as many people with syphilis are often asymptomatic or experience very mild symptoms. Screening can be done in the first trimester using non-treponemal tests such as rapid plasma regain (RPR) or Venereal Disease Research Laboratory (VDRL), and can then be confirmed with treponemal tests such as (Treponema pallidum haemagglutination assay (TPHA) or fluorescent treponemal antibody absorption (FTA-ABS). All pregnant women who are tested positive for syphilis should promptly receive Benzathin penicillin G as the first-line treatment. Screening and treatment of syphilis in early pregnancy may help reduce morbidity and mortality of congenital syphilis.